Association of urine autoantibodies with disease activity in systemic lupus erythematosus - Yuxian Zhang; Yuxian Zhang; Xiaoxia Qu; Xiaoxia Qu; Lishui Wang; Lijun Song; Lijun Song (Frontiers in Medicine, 2024)
ObjectiveThe presence of urinary autoantibodies in patients with systemic lupus erythematosus (SLE) has been confirmed by several studies; however, the significance of their presence in urine remains unclear. This study aims to further investigate the association between urine autoantibodies and disease activity as well as organ involvement in SLE.MethodsThis cross-sectional study included 89 SLE patients. Data collected included anti-nuclear antibody (ANA), anti-ENA antibodies, and anti-dsDNA antibody levels in both serum and urine, complement (C) 3, C4 levels in serum, SLE disease activity index-2000 (SLEDAI-2000), renal domains of SLEDAI (RSLEDAI) and non-renal SLEDAI (NRSLEDAI).ResultsThe rate of positive urine ANA (uANA) was 33.3% (29/87) among the enrolled patients. Compared to the uANA negative group, the positive group exhibited significantly higher SLEDAI-2000 scores (7.85 ± 5.88 vs. 18.69 ± 6.93, p < 0.001), RSLEDAI scores [0 (0, 4.0) vs. 12.0 (8.0, 16.0), p < 0.001], and NRSLEDAI [4 (2.0, 8.0) vs. 6.0 (4.0, 9.5), p = 0.038]. Patients with positive urine anti-Sm antibody demonstrated significantly elevated SLEDAI-2000 scores compared to those who were negative (25.0 ± 8.80 vs. 10.09 ± 6.63, p < 0.001). Similarly, they also had higher RSLEDAI [16.0 (12.0, 16.0) vs. 4.0 (0, 8.0), p < 0.001] and NRSLEDAI [9.5 (6.0, 13.5) vs. 4.0 (3.0, 8.0), p = 0.012], as well as a greater prevalence of renal involvement compared to their negative counterparts (100% vs. 58.2, p = 0.022). There was a positive correlation between uANA titer and both SLEDAI-2000 (rs = 0.663, p < 0.001) and RSLEDAI (rs = 0.662, p < 0.001). The serum anti-dsDNA antibody level did not exhibit a significant correlation with RSLEDAI (rs = 0.143, p = 0.182). Conversely, the urine anti-dsDNA antibody level demonstrated a significant positive correlation with RSLEDAI (rs = 0.529, p < 0.001).ConclusionUrine ANA is associated with both global SLEDAI and RSLEDAI scores. Urine anti-Sm antibody is associated with an increased incidence of renal involvement in SLE. The urine anti-dsDNA antibody level, rather than the serum anti-dsDNA antibody level, exhibits a significant association with RSLEDAI in SLE.